Scaling up dissemination and adoption of agricultural technologies using innovation platforms - Lessons from Eastern and Central Africa - Kimenye, L.N.; McEwan, M. (International Potato Center, 2014)
Between 2008 and 2013 the Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA), was coordinating and providing leadership in the implementation of a project called “Dissemination of New Agricultural Technologies in Africa” (DONATA) across six countries in eastern and central Africa. The approach in DONATA was the innovation platform for technology adoption (IPTA). At the start of the project, there were very limited documented practical experiences and lessons from which to draw guidance for the implementing teams comprised of national agricultural research systems (NARS). Therefore, an inherent objective in the project was to document achievements, experiences and lessons learned on how the IPTA approach was used to disseminate technologies on orange-fleshed sweet potato (OFSP) and quality protein maize (QPM). The DONATA experiences, the synthesis of lessons and guiding principles presented in this book are therefore a contribution to the growing body of knowledge on the application of IP and value chain framework in AR4D in the region. The information shows how the DONATA project teams in ECA have used the AIS theoretical concepts to establish and manage innovation platforms to disseminate and scale out OFSP and QPM technologies. ASARECA envisages that stakeholders within the region will find the book useful in their efforts to increase the spread and impact of science and technology in smallholder agriculture.